Convalescent Plasma for the Treatment of Severe COVID‐19 Infection in Cancer Patients. (17th September 2020) - Tremblay, Douglas; Seah, Carina; Schneider, Thomas; Bhalla, Sheena; Feld, Jonathan; Naymagon, Leonard; Wang, Bo; Patel, Vaibhav; Jun, Tomi; Jandl, Thomas; Rahman, Farah; Liu, Sean T. H.; et al.
Abstract: Background: Patients with malignancy are particularly vulnerable to infection with Severe Acute Respiratory Disease‐Coronavirus‐2 (SARS‐CoV‐2) given their immunodeficiency secondary to their underlying disease and cancer‐directed therapy. We report a case series of patients with cancer who received convalescent plasma, an investigational therapy for severe Coronavirus Disease 2019 (COVID‐19). Methods: Patients with cancer were identified who received convalescent plasma. Enrolled patients had confirmed COVID‐19 with severe or life‐threatening disease and were transfused with convalescent plasma from donors with a SARS‐CoV‐2 anti‐spike antibody titer of ≥ 1:320 dilution. Oxygen requirements and clinical outcomes of interests were captured as well as laboratory parameters at baseline and 3 days after treatment. Results: We identified 24 patients with cancer, 14 of whom had a hematological malignancy, who were treated with convalescent plasma. Fifteen patients (62.5%) were on cancer‐directed treatment at the time of COVID‐19 infection. After a median of hospital duration of 9 days, 13 patients (54.2%) had been discharged home, 1 patient (4.2%) was still hospitalized, and 10 patients had died (41.7%). Non‐intubated patients, particularly those on nasal cannula alone, had favorable outcomes. Three mild febrile non‐hemolytic transfusion reactions were observed. C‐reactive protein significantly decreased after 3 days of treatment, while other laboratory parameters including ferritin and D‐dimer remained unchanged. Conclusions: Convalescent plasma may be a promising therapy in cancer patients with COVID‐19. Abstract : Patients with cancer are particularly vulnerable to infection with COVID‐19 given immunodeficiency secondary to their underlying disease and cancer‐directed therapy. Here, we report a case series of 24 cancer patients with COVID‐19 treated with convalescent plasma. Non‐intubated patients, particularly those on nasal cannula alone, had favorable outcomes, suggesting convalescent plasma may be a viable treatment options for cancer patients with COVID‐19, particularly if utilized early in the disease course.